2013
DOI: 10.5539/ijbm.v8n8p79
|View full text |Cite
|
Sign up to set email alerts
|

Organizational Commitment and Turnover Intentions: Impact of Employee’s Training in Private Sector of Saudi Arabia

Abstract: The purpose of this paper is to investigate impacts of training on organizational commitment and turnover intentions in private sector of Saudi Arabia. The study seeks to focus the relationship between organizational commitment and turnover intentions of the employees. A literature review of organizational commitment and employee turnover provides the basis for the research model and hypotheses. A self-administered questionnaire was used, involving 251 respondents from leading private organizations of Saudi Ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
79
1
18

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(127 citation statements)
references
References 53 publications
(58 reference statements)
11
79
1
18
Order By: Relevance
“…This study showed if employees were committed to the organization, they would maintain membership in the organization and would not be looking for another job. This finding was consistent with the attribution theory which stated that the actions of employees doing the turnover intention could be sourced from employees' internal factors that was organizational commitment (Meyer et al, 2002;Salleh et al, 2012;Biantoro & Sihombing, 2012;Jehanzeb et al, 2013;Nazenin & Palupiningdyah, 2014;Saeed et al, 2014;Yasmin & Marzuki, 2015).…”
Section: Regression Analysissupporting
confidence: 78%
See 1 more Smart Citation
“…This study showed if employees were committed to the organization, they would maintain membership in the organization and would not be looking for another job. This finding was consistent with the attribution theory which stated that the actions of employees doing the turnover intention could be sourced from employees' internal factors that was organizational commitment (Meyer et al, 2002;Salleh et al, 2012;Biantoro & Sihombing, 2012;Jehanzeb et al, 2013;Nazenin & Palupiningdyah, 2014;Saeed et al, 2014;Yasmin & Marzuki, 2015).…”
Section: Regression Analysissupporting
confidence: 78%
“…These results imply if the employees have a strong commitment to the organization, it will affect on the decrease of turnover intention (Meyer et al, 2002;Salleh et al, 2012;Haryokusumo, 2012;Biantoro & Sihombing, 2012;Jehanzeb et al, 2013;Oktaviani & Nurhayati, 2014;Saeed et al, 2014;Yasmin & Marzuki, 2015). Based on previous review studies and explanations, the third hypotheses proposed in this study is: H3: Organizational Commitment has negative effect on Turnover Intention…”
Section: The Effect Of Organizational Commitment On Turnover Intentionmentioning
confidence: 99%
“…Previous studies proved training contributes to intangle results such as high organizational-based self esteem, enhanced organizational commitment and improved participant knowledge and ultimately could affect employee retention and enhance organizational effectiveness (Babu & Reddy, 2013;Jehanzeb et al, 2013;Armstrong, 2006;Ahmad & Bakar, 2003;Bartlett & Kang, 2004;). It is further supported by Ashar, Ghafoor, Munir, and Hafeez (2013) that organization required to manage training on employees with integrity which can enhance the commitments and prevent intention to leave.…”
Section: Training and Developmentmentioning
confidence: 99%
“…It is reciprocal attitudes and behaviors from the employees based on their perception to the effort of the organization in improving their skills, competencies and providing them future development opportunities (Jehanzeb, Rasheed, & Rasheed, 2013;Dockel, Basson, & Coetzee, 2006). It is argued that employees tend to perceive that organization make investment in their training as sign of continuity in their jobs and in higher compensation based on human capital theory (Scheible & Bastos, 2013;Maurer & Rafuse, 2001).…”
Section: Training and Developmentmentioning
confidence: 99%
“…Turnover intention has been described as the last in a sequence of withdrawal cognitions, a set of cognitions include thinking of quitting and the intent to search for alternative employment. Turnover intention refers to an employee's intention to voluntarily leave an organization ( (Jehanzeb, Rasheed, & Rasheed, 2013). In this study, turnover intention is operationalised as employee's intention to voluntarily leave the Unilever Corporation.…”
mentioning
confidence: 99%